ANALISA PENGARUH FOOD VLOGGER DAN DIGITAL MARKETING TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH BRAND AWARENESS - Rita, Rita; Sonia Hendrawati; Ana Yanovi (Bajang Institute, 2025)
As time goes by, especially in the era of globalization, the world has developed very rapidly, especially in the development of technology and the internet. One of the impacts of technological developments in the food and beverages industry, especially coffee shops which use internet platforms as a marketing base. Food vloggers have become an option for businesses to compete for consumers in the industry. This research uses quantitative methods and data collection techniques by distributing questionnaires using Google Form media and using non-probability sampling methods. The sample taken for this research was 110 respondents. Data were analyzed using structured equation modeling-partial least squares (PLS-SEM) with SmartPLS3 software. The research results show that there is a positive influence between food vloggers on brand awareness, food vloggers on purchase intention, digital marketing on brand awareness and brand awareness on purchase intention. Meanwhile, digital marketing does not have a positive influence on purchase intention. Apart from that, the brand awareness variable does not mediate the relationship between food vloggers and purchase intention, but brand awareness indirectly mediates the relationship between digital marketing and purchase intention